Comparative of wear resistance of low carbon steel pack carburizing using different media - Hassan, Kharia Salman (International Journal of Engineering and Technology, 2015)
In this study, various carburizing compounds charcoal, cow bone, CaCO3 were added as energizer for the carburizing compounds in percentage of 10%. To produce another compound to pack carburized mild steel 1020 AISI for investigates the influence of these compounds on wear resistance.Many Cylindrical specimens for the adhesion wear tests were prepared from the used metal with dimensions (10x20mm) according to ASTM (G99-04) specificationsThree Heat Treatment process namely pack Carburizing Quenching, and Tempering were done. Firstly the mild steels specimens are carburized at 925° C for 2hr as soaking time and slow cooling in furnace then carburizing specimens were re heating to 870 °C for half hr. and water Quenching .Tempering was done at 160°C for 1 hour and air cooled. the Carburized and Tempered mild steels are subjected for different kind of test such as Adhesive Wear Test with pin on desk method, Hardness Test were taken using Vickers micro-hardness tester and optical microscope is used for microstructure examination X-ray diffraction for phases observation.The result showed that all carburizing compound were contributed in increasing wear resistance and the compound of cow bone with 10% CaCO3 as energizer had a carburizing case depth of 2.32 mm which gives the highest wear resistance while charcoal compound gives a case depth of 1.1 mm .The work shows that cow bone can be used as compounds and energizer in pack carburization of mild steel. The hardness profile plot of the 90 wt.% 10% caco3 cow bone carburized mild steel was also higher than the other compositions and this value contributed on improvements of wear resistance.